How the ASCENT model can help optimize exposure therapies for Autistic clients - Brook, Amara (Frontiers in Psychiatry, 2025)
Exposure therapies are very effective for alleviating anxiety, yet limited research has focused on optimizing their effectiveness for Autistic clients. This “Perspective” article describes how the ASCENT model can guide tailoring exposure therapies to be more effective and affirming for Autistic clients. This model proposes supporting clients in Autonomous and Affirming goal setting (A), adapting for differences in Sensory processing, Stimming, Structure, Special interests (S), Communication (C), and Executive functioning (E), practicing with Neurohumility (N), and being Trauma informed (T). Because the ASCENT model is based on traits of Autistic clients and effective ways of working with them, it can help guide tailoring a wide variety of anxiety treatments. This article provides examples of how the ASCENT model can be applied to increase the effectiveness of several different types of exposure therapies, as well as articulating when exposure is not appropriate and accommodation is necessary instead.